The Relevance of Adolescent Affective Development Characteristics to Moral Decadence in Schools - Hafizh, Muhammad; Falakhina, Arum Nela; Jauhari, Roshifah (An-Nuha, 2025)
The academic problems in this research are in the form of moral problems in the world of education that have not been resolved properly, so there needs to be a review related to affective in adolescence to morals in schools because the better the affective aspect among adolescent students, the better the morals. This research is included in qualitative-library research with a descriptive causal analysis method to explore and identify the relationship between adolescent affective aspects such as emotions, attitudes, values, and feelings with symptoms of moral decadence that occur among them. The results of the study show that juvenile delinquency in the school environment is a manifestation of moral decadence that correlates with the characteristics of the development of the affective domain of adolescents, where changes in the domain that are not handled appropriately contribute to deviant behavior that violates social norms.